Nanopartículas de ouro aplicadas em células solares de perovskita - Rosa, Eduardo Henrique dos Santos (2024)
Currently, non-renewable sources for electricity generation account for the largest share of electricity production, contributing to increased rates of environmental degradation. Against this backdrop, there is a need to develop new research that contributes to producing electricity from renewable sources with a high energy demand. Among the existing technologies is photovoltaic energy, which converts the energy of the sun into electricity, an abundant and free resource to capture. The growing demand for clean and renewable energy sources has led to the development and improvement of perovskite solar cell (PSC) technology, which has an energy conversion efficiency of around 26.7% and exciting features such as low cost, transparency, lightness, and can be processed on flexible substrates. However, these devices show reduced stability when exposed to the ambient atmosphere due to the interaction of the active layer and intermediates with oxygen, humidity, and impurities that contribute to the degradation of the solar cell. Aiming to improve the stability of PSCs when exposed to air, in this work, gold nanoparticles (AuNPs) produced by the laser ablation in suspension method (LASis) were applied in two distinct ways: at the hole transport layer (HTL) and in the active layer. In the modification of the HTL, the AuNPs were produced in isopropanol (IPA) and processed onto the Spiro-OmeTAD layer. This material must use additives to improve its electrical properties and guarantee good conductivity. Among the used additives, LiTFSI salt performs an essential role in enhancing the hole mobility of the layer, although it is hygroscopic and absorbs air moisture, degrading the photovoltaic device. The analysis of the modified devices using atomic force microscopy (AFM) shows the precipitation of the TFSI- anion along the top surface, with this process depending on the exposure time in the air, resulting in the reduction of the stability during the operation time. Therefore, two procedures were adopted: washing the surface of Spiro-OmeTAD with IPA and depositing the suspension of AuNPs in IPA onto the HTL. The modification with AuNP decreased the precipitation of the hygroscopic additive to the top surface, increasing the water contact angle. Spectroscopy Raman measurements suggest the coordination of the TFSI- anion in two distinct ways, in Li or AuNPs, with Raman shift bands in 747 cm-1 e 751 cm-1, contributing to the stabilization of the additive and avoiding its interaction with H2O molecules. Using the AFM technique, the contribution of the IPA solvent was found, which helps in the morphology improvement of the HTL by decreasing the root mean square roughness (Rrms) and superficial defects. The morphology improvement resulted in more efficient devices after 48h of air exposure due to the shielding effect of the AuNP and its interaction with the hygroscopic additive, resulting in more stable and efficient PSCs, even when exposed to air for 35 days with high relative humidity in the air. In the second approach, AuNPs produced with chlorobenzene (CB) were processed in the active layer by being introduced into the perovskite (PSK) antisolvent. Morphological analysis indicates the increase in the grain size for the modified thin films with AuNPs due to the heterogeneous nucleation induced by the nanoparticles, which act as nucleation seeds and perovskite grain growth. Bigger grains result in fewer grain boundaries and, therefore, fewer propitious spots for the infiltration of impurities, such as H2O molecules. In-situ GIWAXS analysis shows a faster nucleation process by the appearance of cubic perovskite peaks and the no-presence of PbI2 peaks during the film nucleation, resulting in an improved crystallization process. The GIWAXS analysis also reveals that the modification with AuNP leads to a more significant presence of cubic perovskite phase in the interface between PSK/ HTL. The modified devices with different AuNP contents in the antisolvent were monitored in the air for 1000h. They showed superior performance compared to control devices and were more stable due to the heterogeneous nucleation process by using AuNP. Moreover, modified devices showed a decrease in the hysteresis index, which can be related to the charge accumulation in interfaces and the fact that the highest concentration of the cubic phase was observed in the interface between PSK/ HTL.Using the UV-Vis technique, an improvement in the thin film absorbance for the modified samples was observed, which contributes to the superior performance of these devices.